SERUM HOMOCYSTEINE CONCENTRATIONS INVERSELY CORRELATES TO INTIMA-MEDIA THICKNESS OF CAROTID ARTERIES: AN IMPACT TO ENVERSE EPIDEMIOLOGY IN PRE-DIALYTIC CHRONIC KIDNEY DISEASE - Raka-Widiana, I G.; Suwitra, K.; Elyshanti, E.; Sutarka, and N. (BALI MEDICAL JOURNAL, 2013)
Background: In normal population, serum homocysteine (Hcy) is considered as a marker of atherosclerotic and cerebro-cardiovascular diseases.  It is not clear whether this phenomenon also occurs in chronic kidney disease particularly among pre-dialytic population. This study aims to determine relationship between serum Hcy concentrations and carotid arteries intima-media thickness (CA-IMT) of pre-dialytic chronic kidney disease (CKD) patients. Method: A cross-sectional study was carried out on pre-dialytic CKD patients. Morning fasting blood samples were taken for lipid profile, blood sugar, blood urea nitrogen, serum creatinine concentrations. Total fasting serum Hcy concentrations were measured using chemiluminescent assay. CA-IMT of patients were measured by USG B-Mode Logiq-5 (General Electric), with 7.5 MHz linear transducer at both left and right, common and bifurcation of carotid arteries. Results: Ninety (74 males, 16 females) of pre-dialytic patients, age 54 ± 7 years, SBP 137±20 mmHg, DBP 78±13 mmHg, BMI 23.9±4.4 kg/m2 FBS 94±16 mg/dL and 2h pp BS 125±31 mg/dL, total-C 201±65 mg/dL, LDL-C 129±62 mg/dL, HDL-C 40±13 mg/dL, TG 144±81 mg/dL, phosphate 3.8±1.3 mg/dL, calcium 8.7±1.1, and CaXP 32±8, and total serum Hcy 17.11±6.91 µmol/L, e-GFR (CG formula) 36±17 ml/minutes were included in this study.  There were significant negative correlation between Hcy concentrations and left common CA-IMT (r = 0.28; B = -11.01; p = 0.02) and right bifurcation CA-IMT (r =0.26; B = -11.01; p=0.042). While there were a trend of negative correlation between total serum Hcy and right common CA-IMT (r= 0.21; B = -8.27; p=0.10) and left bifurcation CA-IMT (r= 0.20; B=-6.69; p=0.11). Conclusion: There is a negative association between total serum Hcy concentrations and atherosclerotic process in carotid arteries. The inverse relationship may support phenomenon of inverse epidemiology among pre-dialytic CKD patients and seemed that serum Hcy reflects nutritional marker rather than a marker of cardiovascular disease.